A rapid solid-phase enzyme-linked binding assay for screening monoclonal antibodies to cell surface antigens. - Cobbold, S; Waldmann, H (1981)
A solid-phase enzyme-linked binding assay is described for screening monoclonal antibodies to cell surface antigens. E. coli beta-galactosidase was coupled to rabbit anti-rat Ig and used to detect the binding of rat monoclonal antibodies to cells which had been fixed to the wells of microtitre plates using a combination of poly-L-lysine and glutaraldehyde. This method was found to be advantageous for the large screening of monoclonal antibodies with a panel of cell types, and has been useful in the selection of antibodies which would be candidates for differentiation markers within the human and mouse haemopoietic systems.